Nilai Kehidupan dan Gaya Bahasa Pada Puisi “Dengan Puisi Aku” Karya Taufiq Ismail - Lula Mulyani (Concept: Journal of Social Humanities and Education, 2022)
The poem "With My Poetry" is one of the literary works by Taufiq Ismail that describes the author's feelings in writing the poem, this poem is included in one of the literary works that have aesthetic value in the world of art. The purpose of this study was to determine the value of life and the type of language style used in Taufik Ismail's poem "With Puisiku". The research method used in this article is a qualitative descriptive research method. From the results of this study, the value of life contained in this poem is a reflection of life about how the next life will go well, and the style of language in the poem "With Puisi Aku" by Taufiq Ismail, namely: Alliteration, Assonance, Simile, Personification, Sarcasm, and Anophora.